Destabilization of ultrafine bubbles in water using indirect ultrasonic irradiation - Shunya Tanaka (Ultrasonics Sonochemistry, 2021)
Ultrafine bubble (UFB) is a bubble with a diameter of less than 1 μm. Little attention has been paid to the defoaming and removal of UFBs. This study proposes a method to destabilize UFBs by using indirect ultrasonic irradiation. Besides, the destabilization mechanism of UFB was investigated. The ultrasonic frequency was 1.6 MHz and the dissipated power was 30 W. UFB dispersions were prepared using two different types of bubble generators: pressurized dissolution method and swirling liquid flow method. The effects of ultrasonic irradiation on the stability of UFBs were evaluated by particle tracking analysis (PTA) and electrophoretic zeta potential measurement. Results showed that the indirect ultrasonic irradiation for 30 min reduced the number concentration of UFBs by 90% regardless of the generation method. This destabilization was attributed to a decrease in the magnitude of zeta potential of UFBs due to the changes in pH and electrical conductivity. These changes in the electrochemical properties were caused by the formation of nitric acid. To study the destabilization mechanism, the pH of the UFB dispersions were modified by titration; the chemical and mechanical effects of ultrasound were separately examined. It was found that not only the chemical effect caused by the formation of nitric acid but also the mechanical effect contributed to the destabilization of UFB. Feasibility studies were also performed for UFBs in an aqueous surfactant solution and UFBs in a solid particle dispersion. The proposed method selectively destabilized UFBs in the solutions.